THE IMPORTANCE OF PATRIOTIC STUDY IN EDUCATING YOUTH IN PATRIOTIC SPIRIT - Khasanov. Kh. Kh (American Journals, 2024)
In this article, there are thoughts and opinions about educating young people in the spirit of patriotism. One of the leading, main components of high spirituality is patriotism. Therefore, the concept of patriotism is approached and interpreted differently. In our opinion, patriotism means that a person values his motherland and spends his energy and energy for this motherland, regardless of its field. Although this definition does not cover all aspects of patriotism, the definition is correctly understood if the word patriotism is approached in a broad sense.
Keywords: youth, patriotism, values, loyalty, concept of homeland, education and training